2003
DOI: 10.1162/089976603765202659
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Rhythmic Bursts: Coherence Control in Networks of Cortical Pyramidal Neurons

Abstract: Much evidence indicates that synchronized gamma-frequency (20-70 Hz) oscillation plays a significant functional role in the neocortex and hippocampus. Chattering neuron is a possible neocortical pacemaker for the gamma oscillation. Based on our recent model of chattering neurons, here we study how gamma-frequency bursting is synchronized in a network of these neurons. Using a phase oscillator description, we first examine how two coupled chattering neurons are synchronized. The analysis reveals that an increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 53 publications
(77 reference statements)
5
18
0
Order By: Relevance
“…In the hippocampus, synchronous gamma oscillation is considered to occur through the GABA A receptor-mediated mutual inhibition among interneurons [Buhl et al, 1994;Cobb et al, 1995;Freund and Buzsaki, 1996]. In the neocortex; it is known that a class of pyramidal neurons termed fast rhythmic bursting cells or "chattering" neurons synchronize their activities at gamma frequencies and are thought to be necessary for selective attention or binding processing in object recognition [Aoyagi et al, 2003]. Therefore, a slight disruption of the balance between excitation and inhibition in the cortex could have dramatic consequences on the function of the neuronal networks underlying perception and attention.…”
Section: Chapel Hill North Carolinamentioning
confidence: 99%
“…In the hippocampus, synchronous gamma oscillation is considered to occur through the GABA A receptor-mediated mutual inhibition among interneurons [Buhl et al, 1994;Cobb et al, 1995;Freund and Buzsaki, 1996]. In the neocortex; it is known that a class of pyramidal neurons termed fast rhythmic bursting cells or "chattering" neurons synchronize their activities at gamma frequencies and are thought to be necessary for selective attention or binding processing in object recognition [Aoyagi et al, 2003]. Therefore, a slight disruption of the balance between excitation and inhibition in the cortex could have dramatic consequences on the function of the neuronal networks underlying perception and attention.…”
Section: Chapel Hill North Carolinamentioning
confidence: 99%
“…Since the mathematical details of this model have been published elsewhere (Aoyagi et al 2002(Aoyagi et al , 2003, below we list only the parameter values that were different from the previous ones: T = 309.16, K CAN = 13.16 μM and g CAN = 113 or 170 (two types of doublet) mS/cm 2 .…”
Section: Single-compartment Can Current Modelmentioning
confidence: 99%
“…Our previous study of single-compartment CAN current model has revealed that PRCs for burst firing can in general show a broad peak in the inter-burst interval and a sharp peak in the interval within a burst (Aoyagi et al 2003). The two peaks play differential and PRCs (lower panels) during one bursting cycle were calculated in singlet, doublet near the singlet, doublet near the triplet, and triplet bursting states, respectively, using a neuron model proposed by Izhikevich (2003).…”
Section: Artificial Prcs Of Doublet Burstingmentioning
confidence: 99%
See 2 more Smart Citations